2021
DOI: 10.9778/cmajo.20200236
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve the well-being of medical learners in Canada: a scoping review

Abstract: C oncerns exist about the impact of medical education on learner well-being. [1][2][3][4] Programs housed within medical schools often address intellectual and occupational well-being, focusing specifically on skills related to learning and working; 5,6 however, well-being is a multidimensional construct. Social, mental, and physical wellbeing have been shown to be negatively affected during undergraduate medical education, 7 with increased prevalence of burnout in residency. 8,9 Poor well-being can affect med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 130 publications
1
2
0
Order By: Relevance
“…24 We also learned that our participants scored within a range of poor overall wellbeing, and our findings complement other research which suggests that medical training is a unique risk factor for poor wellbeing which is further compounded by barriers to self-disclosure. 1,2,25,26 Our participants confirmed the persistent double standards and perceived hypocrisy in medical education and that these double standards and fear of disclosure appears to worsen over time. 27 For example, in our study resident OMS-HC scores and qualitative findings demonstrated fear of judgment among medical students become fear of retribution or adverse career consequences for learners.…”
Section: Disclosure Experiences Varied Based On Individuals' Intersec...supporting
confidence: 61%
“…24 We also learned that our participants scored within a range of poor overall wellbeing, and our findings complement other research which suggests that medical training is a unique risk factor for poor wellbeing which is further compounded by barriers to self-disclosure. 1,2,25,26 Our participants confirmed the persistent double standards and perceived hypocrisy in medical education and that these double standards and fear of disclosure appears to worsen over time. 27 For example, in our study resident OMS-HC scores and qualitative findings demonstrated fear of judgment among medical students become fear of retribution or adverse career consequences for learners.…”
Section: Disclosure Experiences Varied Based On Individuals' Intersec...supporting
confidence: 61%
“…Wellbeing interventions are needed to address the complex and broad-ranging issues that members of FoMs may face. While most FoMs excel in addressing students’ cognitive, occupational, and social needs, their mental, emotional, and physical needs are often overlooked [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Similarly, personal counseling is often student-initiated when a life event or other acute stressor threatens the student’s academic progress. 27,28 In these as well as in many other points of interaction with student affairs faculty and staff, the onus of seeking support and coordinating between the various services falls on the student. The limitations of these practices are highlighted by reframing both examples with a proactive approach: being paired with an academic counselor or tutor at the time of enrollment, with the pairing being guided by a thorough handoff from the admissions team that details the specific learning needs with which the student matriculated, and concurrently, being connected with a personal counselor to cultivate skills for addressing stressors originating from the student’s unique complement of lived experiences, which may be heightened during their medical training.…”
mentioning
confidence: 99%